Faktor-Faktor Yang Mendorong Minat Beli Smartphone Merek OPPO Dalam Kondisi Pandemi Covid-19 - Sudirman, Acai; Halim, Fitria; Pakpahan, Grace Endang; Sherly, Sherly (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2020)
The use of smartphones currently grows rapidly and has become a necessity in everyday life. Compared to the past, the basic use of cell phones is only for making phone calls or sending messages, but the function of the smartphone today has improved in terms of its usefulness to meet social needs. However, looking at the recent condition of the COVID-19 Pandemic, it is totally contradicted with the growing trend of internet use. Some smartphone companies experienced a decrease in sales due to lower economic activity, which has implications in decreased people’s purchasing power. The objective of this study was to determine the factors that can encourage consumer buying interest, consisting of product quality, price, and brand experience. The data analysis obtained from the research object used a survey model with a quantitative approach. The number of samples obtained as respondents was 240 people. The data were analyzed using validity and reliability tests by the outler model and the SEM structural model as a representative of the inner model. Based on the results of the study, it was found that the quality of the product had no effect on buying interest. Price had a significant effect on buying interest. Brand experience had a significant effect on buying interest.